2018
DOI: 10.3389/fendo.2018.00014
|View full text |Cite
|
Sign up to set email alerts
|

DHEA Supplementation Confers No Additional Benefit to that of Growth Hormone on Pregnancy and Live Birth Rates in IVF Patients Categorized as Poor Prognosis

Abstract: BackgroundIn vitro fertilization (IVF) patients receive various adjuvant therapies to enhance success rates, but the true benefit is actively debated. Growth hormone (GH) and dehydroepiandrosterone (DHEA) supplementation were assessed in women undergoing fresh IVF transfer cycles and categorized as poor prognosis from five criteria.MethodsData were retrospectively analyzed from 626 women undergoing 626 IVF cycles, where they received no adjuvant, GH alone, or GH–DHEA in combination. A small group received DHEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…This may mean that alternative, weaker studies, such as retrospective cohort studies, may be required to advance the field provided they are stringently designed, conducted and analysed. Two recent retrospective studies by our group showed that CP and LB rates were significantly greater with GH (3.42-fold and 6.16-fold higher, respectively) following the transfer of fresh autologous embryos in stimulated cycles [12,13]. Age at embryo transfer (ET) and morphological quality of the transferred embryo were the only other significant independent predictors of the likelihood of CP and LB, but no significant differences were observed in the proportion of high-quality embryos generated in the GH arm, echoing the most recent prospective study [8].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…This may mean that alternative, weaker studies, such as retrospective cohort studies, may be required to advance the field provided they are stringently designed, conducted and analysed. Two recent retrospective studies by our group showed that CP and LB rates were significantly greater with GH (3.42-fold and 6.16-fold higher, respectively) following the transfer of fresh autologous embryos in stimulated cycles [12,13]. Age at embryo transfer (ET) and morphological quality of the transferred embryo were the only other significant independent predictors of the likelihood of CP and LB, but no significant differences were observed in the proportion of high-quality embryos generated in the GH arm, echoing the most recent prospective study [8].…”
Section: Introductionmentioning
confidence: 88%
“…In our practice, poor-prognosis women can receive GH or other IVF adjuvant (dehydroepiandrosterone [DHEA]) treatment in stimulation cycles if they have one of the following characteristics: age ≥ 40 years, generating ≤ 3 metaphase II oocytes despite high folliclestimulating hormone (FSH) stimulation doses ( ≥ 300 IU), > 50% poorquality embryos, repetitive implantation failure (RIF) in ≥ 3 ETs without achieving pregnancy, and a low ovarian reserve (antral follicle count [AFC] ≤ 8 or anti-Müllerian hormone [AMH] level ≤ 8 pmol/L), designated as AFC groups D and E in our published recombinant FSH dosing algorithms [19,20]. These criteria have been published previously for fresh ET cycles, with group B/C corresponding to 9-19 folli-cles inclusive and group A equating to 20 or more follicles [12,13]. In the current FET study, patients receiving or having a medical history of receiving IVF adjuvants (GH or DHEA) were considered to have a poor prognosis for the above reasons.…”
Section: Study Cohort and Definition Of Poor-prognosis Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, different protocols have been suggested to improve outcomes in those patients, such as: the use of nitric oxide, formed in vivo from L-arginine, which may play a role in follicular maturation and ovulation. Growth hormone is also employed to regulate the effect of FSH, increasing the synthesis of insulin-like growth factor and consequently ovarian function, quality, and embryo implantation [15][16][17].…”
Section: Poor Responder Patientsmentioning
confidence: 99%
“…These hormones bind to a specific receptor on the cell membrane of the effector organ, activating an intracellular enzyme, the adenylyl cyclase, responsible for converting adenosine triphosphate (ATP) into cyclic adenosine monophosphate (cAMP). The cAMP, in turn, binds to a cytoplasmic protein (guanine nucleotide binding proteins-G protein), and this newly formed complex is responsible for the activation of the enzymes involved in steroidogenesis [17,18].…”
Section: Steroidogenesismentioning
confidence: 99%